2012
DOI: 10.7575/ijalel.v.1n.2p.170
|View full text |Cite
|
Sign up to set email alerts
|

Oral Communication Skills of Engineering Students of Pakistan in Perspective of Industrial Internships

Abstract: The purpose of this study was to determine impact of industrial internship training on oral communication skills of engineering students during this program. Fifty engineers from two engineering organizations participated in this study. Participants of this study had industrial internship training from different organizations. Purposive sampling method was used for data collection purpose. The results of the study revealed that industrial internship trainings contribute to develop oral communication skills of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The finding showed that oral communication was strongly needed by the engineering students at UMM. And this is similar to the findings of Zaid and Kamarudin [39], Kakepoto et al [40], Bhattacharyya [8], Araminta and Halimi [5], Lan, Proust, and Lim, [41].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding showed that oral communication was strongly needed by the engineering students at UMM. And this is similar to the findings of Zaid and Kamarudin [39], Kakepoto et al [40], Bhattacharyya [8], Araminta and Halimi [5], Lan, Proust, and Lim, [41].…”
Section: Discussionsupporting
confidence: 91%
“…Kakepoto et al [40] claimed that engineering students should develop their English communication skills such as those for oral presentation, meeting, discussion, conversation, and project participation. In addition, Bhattacharyya [8] reported that engineers need to master both interdisciplinary and interpersonal competence in order to be effective leaders in the global workplaces mainly in the area of teamwork, critical thinking, decision making, and communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers consider setting criteria for the sample is a necessity to increase adequacy of the study (Muhwezi, Acai, & Otim, 2014). Additionally, Kakepoto et al (2012) suggest that setting a limitation in terms of working experience is essential, due to the gained understanding and perception of communication and feedback during this period. Thus, for the purpose of this research, sampled respondents must possess at least two years of experience of practising architecture, designing and dealing with clients within their practice.…”
Section: Methodsmentioning
confidence: 99%
“…To gain more experience through increasing the years of working and dealing with clients can enhance the architects' ability to understand the clients' needs and to properly manage to communicate, explain and exchange information with them (Kakepoto et al, 2012 As communication methods and techniques vary according to the project, cooperation and effective communication with clients have a direct impact on the project success, where insufficient collaboration is an impactful cause of low-end innovation (Holmen, Pedersen, & Torvatn, 2005). Architecture is the core of the world of visualization, and 3D renderings or perspective drawings are considered to be a critical approach of communication between the client and the architect (Kitchens & Shiratuddin, 2007;Shen, 2011).…”
Section: Agementioning
confidence: 99%
“…Studies concurred that communication skills (oral and written) represented a highly important competency for engineers' professional practice [33][34][35]. However, while internship experiences generally contributed to the enhancement of the interpersonal and oral communication skills of engineering students [36,37], their contributions to writing skills were less obvious [31,32,38,39]. In a study that probed senior engineering students' knowledge about design processes, Bailey found that industrial experience made a positive difference to learning in only one knowledge areadocumentation [40].…”
Section: Theme 1 (Regarding the Learning Outcomes) Co-ops And Internmentioning
confidence: 99%